Formylation of initiator tRNA methionine in procaryotic protein synthesis: in vivo polarity in lactose operon expression. - Petersen, H U (1978)
Eucaryotic and procaryotic organisms differ in two aspects of their translation machinery: polycistronic messengers are expressed as a sequence of individual proteins only in procaryotes, and the initiation of protein synthesis proceeds with an initiator tRNA which is found to be modified (formylated) in procaryotes and not in eucaryotes. In the present study, we show that formylation is required in vivo for the coordinate expression of the Escherichia coli lactose operon. Our experiments are consistent with a translation mechanism using dissociated ribosomes at the 5' end of the mRNA in a reaction that is only weakly dependent on formylation at this initiation step; the ribosomes then travel along the messenger and can reinitiate after the intracistronic barrier without dissociation. This latter initiation step is strongly dependent on the level of formylation: a low level of the formyl group, obtained by the antifolic agent trimethoprim, induces a strong polarity in the expression of the lactose operon. There exist mutant strains in which this polarity is much less apparent than in the wild type. We show here that such is the case of rpsL mutants. Ribosomes mutated in the S12 protein (rpsL) are found to be much more easily dissociated than the wild type. This might explain why the expression of the lactose operon on rpsL strains remains coordinated when the intracellular level of formylation is decreased.